Perencanaan Strategis Sistem Informasi Dan Teknologi Informasi Pada PT Goldfindo Intikayu Pratama Dengan Menggunakan Tahapan Anita Cassidy - Irawan, Sara Zetira; Sudarmaningtyas, Pantjawati; Sutomo, Erwin (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
PT Goldfindo Intikayu Pratama is a company engaged in the production of furniture, such as furniture for household and office supplies. The company's main processes namely, marketing and sales, purchasing, and production. Problems faced by the company is the systems and information technology (SIT) that failed to implement because it can not help in running the business processes of the company, so it can not align business processes with existing SIT. The failure in the implementation of the SIT cause the company suffered losses in developing SIT. Efforts are needed to improve the situation is to make strategic planning SIT, it aims to be able to align the company's business processes with SIT. Therefore, this study uses the stage Anita Cassidy and using analytical methods such as value chain analysis, SWOT, Five Forces Model, Portfolio McFarlan, Owners Estimate that can help identify and analyze SIT that is consistent with the company's business. The results of this study in the strategic planning documents STI which includes 12 SIT projects, the total estimated cost of Rp 192 900 061 SIT, SIT portfolio, there are directives SIT developments and there is a SIT roadmap for the next 3 years starting from 2017 to 2019.